International Prostate Symptom Score: Really Appreciated by All Patients or Not? - Öztürk, Metin Ishak; Koca, Orhan; Keles, Muzaffer Oguz; Günes, Mustafa; Kaya, Cevdet; Karaman, Muhammet ?hsan (Urology Journal, 2011)
Purpose: To investigate the relationship between the accuracy of the answers provided by the patients to the International Prostate Symptom Score (IPSS) questionnaire and age and level of education. Materials and Methods: Two hundred and thirty-eight men were given self-administered IPSS questionnaires. After 48 to 96 hours, the IPSS form was completed again with the assistance of a physician. The relationship of the difference between the self-administered IPSS and forms completed with assistance with age and level of education was evaluated through Wilcoxon test. P values less than .05 were considered significant. Results: There was not a significant difference between the two IPSS among the high school or university graduates (P = .480). However, the difference was significant among the primary and secondary school graduates (P = .042 and P = 0.34, respectively). Of values obtained from self-administered IPSS forms and those completed with the assistance of a physician, there was a statistically significant difference in the group ≥ 60 years of age. Conclusion: Age ≥ 60 years and being primary or secondary school graduate are factors lowering the comprehension of the IPSS by the patients. Older patients and those with lower education could benefit from the assistance of a physician while completing this questionnaire.